The influence of ATM on operating systems. - Smith, Jonathan M. (Computer communication review.)
The features of ATM offered many attractions to the application community, such as fine-grained multiplexing and high-throughput links. These created considerable challenges for the O.S. designer, since a small protocol data unit size (the 48 byte "cell") and link bandwidths within a (binary) order of magnitude of memory bandwidths demanded considerable rethinking of operating system structure.Using an historical and personal perspective, this paper describes two aspects of that rethinking which I participated in directly, namely, those of new event signalling and memory buffering schemes. Ideas and techniques stemming from ATM network research influenced first research operating systems and then commercial operating systems. The positive results of ATM networking, although indirect, have benefitted applications and systems far beyond the original design goals.